ANALISIS KANDUNGAN FORMALIN PADA BAKSO YANG DIPERJUALBELIKAN DI SEKITAR JALAN ABD.KADIR KOTA MAKASSAR - salawati salawati; Andi Auliyah Warsyidah (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
The prohibition on the use of formalin as food additives has been stated in Republic of Indonesia Minister of Health Regulation No. 033 of 2012, but formalin is still often used freely by producers who are not responsible for improving food texture and inhibiting the activity of microorganisms. This study aims to determine the formalin content of meatballs that are traded around Jalan Abd. Kadir, Makassar. This type of research is descriptive research. The research was conducted on 28-29 July 2017 at the University of Eastern Indonesia Pharmacy Laboratory. The population in this study were all meatballs that were traded around Jalan Abd. Kadir. Sampling was done by purposive sampling and determined as many as 5 samples by observing parameters such as texture, elasticity, and color of meatballs. The results of the qualitative examination showed no formalin content in the five meatball samples.